Evaluation Report on Family Planning Programme - Planning Commission (Planning Commission, 1986)
Although the Family planning programme has been in operation in the country for over three decades now it has a vital and continuing importance both from the standpoint of the need to control and stabilise the growth of population and of enhancing the welfare impact of further economic development. It has been adopted as a national programme by the Government of India.
Programme Evaluation Organisation Planning Commission Government of India New Delhi